Sensitivity tests of cosmic velocity fields to massive neutrinos. Issue 3 (4th March 2022) - Zhou, Shuren; Liu, Zhenjie; Ma, Qinglin; Liu, Yu; Zhang, Le; Li, Xiao-Dong; Wang, Yang; Wang, Xin; Yu, Yu; Yu, Hao-Ran; Zheng, Yi
ABSTRACT: We investigate impacts of massive neutrinos on the cosmic velocity fields, employing high-resolution cosmological N -body simulations provided by the information-optimized CUBE code, where cosmic neutrinos are evolved using collisionless hydrodynamics and their perturbations can be accurately resolved. In this study, we focus, for the first time, on the analysis of massive-neutrino-induced suppression effects in various cosmic velocity field components of velocity magnitude, divergence, vorticity, and dispersion. By varying the neutrino mass sum M ν from 0 to 0.4 eV, the simulations show that the power spectra of vorticity – exclusively sourced by non-linear structure formation that is affected by massive neutrinos significantly – are very sensitive to the mass sum, which potentially provide novel signatures in detecting massive neutrinos. Furthermore, using the χ 2 statistic, we quantitatively test the sensitivity of the density and velocity power spectra to the neutrino mass sum. Indeed, we find that the vorticity spectrum has the highest sensitivity, and the null hypothesis of massless neutrinos is incompatible with both vorticity and divergence spectra from M ν  = 0.1 eV at high significance ( P -value = 0.03 and 0.07, respectively). These results demonstrate clearly the importance of peculiar velocity field measurements, in particular of vorticity and divergence components, in determination of neutrino mass and mass hierarchy.